MICRONUTRIENTS AND CHILDREN’S HEALTH - I.М. Kosenko (Вопросы современной педиатрии, 2011)
Nutrient deficiency in children’s food leads to delay in physical and neuropsychic development, increase risk of various diseases. Longstanding deficit of several nutrients in a diet can lead to permanent changes in child’s body. This is vitally important especially in childhood and adolescence — time of most extensive growth and development. The review covers physiological role of vitamins and minerals, especially vitamin-mineral metabolism in children and main reasons of possible deficit of these micronutrients in their diet. Recommendations upon prevention and correction of vitamin-mineral deficit with the use of individually prescribed vitamin-mineral complexes are given in the article.Key words: children, health, micronutrients, vitamin & mineral complexes. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 179–185)